Analysis of the application of biomechanics to the prevention of sports injuries in physical education learning - Muhammad Surur (Universitas Sriwijaya, 2023)
The purpose of this study is to examine the connection between using biomechanics to prevent sports injuries in physical education learning, with a sample size of 10 physical education teachers in Muaragembong sub-district, Kabupaten Bekasi. The method used is descriptive quantitative data collection techniques with open semi-structured interviews and questionnaires. Based on the discussion and research data it can be drawn that physical education teachers who have a high level of understanding are strongly related to the prevention of student sports injuries in physical education learning. Based on two factors that influence the relationship, namely, the biomechanics understanding factor obtained a